Interventions designed to improve the quality and efficiency of medication use in managed care: A critical review of the literature - 2001-2007 - Soumerai Stephen B; Ross-Degnan Dennis; Lu Christine Y; Pearson Sallie-Anne (BMC, 2008)
Abstract Background Managed care organizations use a variety of strategies to reduce the cost and improve the quality of medication use. The effectiveness of such policies is not well understood. The objective of this research was to update a previous systematic review of interventions, published between 1966 and 2001, to improve the quality and efficiency of medication use in the US managed care setting. Methods We searched MEDLINE and EMBASE for publications from July 2001 to January 2007 describing interventions targeting drug use conducted in the US managed care setting. We categorized studies by intervention type and adequacy of research design using commonly accepted criteria. We summarized the outcomes of well-controlled strategies and documented the significance and magnitude of effects for key study outcomes. Results We identified 164 papers published during the six-year period. Predominant strategies were: educational interventions (n = 20, including dissemination of educational materials, and group or one-to-one educational outreach); monitoring and feedback (n = 22, including audit/feedback and computerized monitoring); formulary interventions (n = 66, including tiered formulary and patient copayment); collaborative care involving pharmacists (n = 15); and disease management with pharmacotherapy as a primary focus (n = 41, including care for depression, asthma, and peptic ulcer disease). Overall, 51 studies met minimum criteria for methodological adequacy. Effective interventions included one-to-one academic detailing, computerized alerts and reminders, pharmacist-led collaborative care, and multifaceted disease management. Further, changes in formulary tier-design and related increases in copayments were associated with reductions in medication use and increased out-of-pocket spending by patients. The dissemination of educational materials alone had little or no impact, while the impact of group education was inconclusive. Conclusion There is good evidence for the effectiveness of several strategies in changing drug use in the managed care environment. However, little is known about the cost-effectiveness of these interventions. Computerized alerts showed promise in improving short-term outcomes but little is known about longer-term outcomes. Few well-designed, published studies have assessed the potential negative clinical effects of formulary-related interventions despite their widespread use. However, some evidence suggests increases in cost sharing reduce access to essential medicines for chronic illness.